ViCES - Video Conferencing Educational Services Main Project Outcomes - Caporali, Enrica; Trajkovik, Vladimir (Proceedings e report, 2012)
This e-book has been developed as result of the Video Conference Educational Service (ViCES) project under the TEMPUS action of the European Commission (144650-TEMPUS-2008-IT-JPGR. It is intended to serve as a set of guidelines for the setup and usage of videoconference tools in educational and vocational training institutions. It also offers suggestions to: companies, agencies and institutions that plan to introduce video conferencing based training experiences. The e-book covers both technical and organizational issues related to video conferencing educational services, such as: Learning Methodology Guideline, Non functional Requirements Recommendation, Organizational Structure & Business Processes Recommendation, Service Level Agreement Recommendation, Video Conferencing Service Sustainability Strategy, and Video Conferencing end Station Basic Tutorial.